Organization of Collaborative Work Between Teacher-Speech-Language Pathologist and Parents of Junior Students with Intellectual Disability - Koloskova O. A. (Socio-Cultural and Psychological Problems of the Modern Family: Current Issues of Assistance and Support, 2020)
the article contains methodological recommendations for speech-language pathologist on organization of work with parents of junior students with intellectual disability. Given recommendations will help to inform the parents about the characteristics of the child's speech development, will connect and unite the speech-language pathologist and the parent which will significantly improve the quality and will accelerate the result of logopedic remedial help.
Keywords: умственная отсталость; словарный запас; методические рекомендации; работа с родителями; рекомендации для логопеда; vocabulary; methodological recommendations; intellectual disability; work with parents; speech-language pathologist’s recommendations